2009
DOI: 10.3382/ps.2008-00191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzyme supplementation and acidification of diets on nutrient digestibility and growth performance of broiler chicks

Abstract: Two experiments were conducted to examine the effects of alpha-galactosidase supplementation and acidification of diets on nutrient digestibility and growth performance of broiler chicks. In experiment 1, dietary treatments consisted of feeding a low-energy basal diet (2.74 Mcal of ME/kg) alone, the basal diet supplemented with 1,724 units of alpha-galactosidase per kg, the basal diet supplemented with 2% citric acid, or the basal diet supplemented with both. alpha-Galactosidase significantly increased feed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 29 publications
9
56
0
7
Order By: Relevance
“…These results corroborate the studies of Pirgozliev et al (2008), who observed AMEn improvement in young broilers fed diets supplemented with fumaric acid and sorbic acid, and also corroborate studies conducted by Ao et al (2009), in which citric acid increased the metabolizable dry matter and crude protein. However, Hernández et al (2006) observed no differences in the metabolization of total and ileal dry matter and crude protein in the 16 to 21 day-old period in broilers fed two levels of formic acid.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…These results corroborate the studies of Pirgozliev et al (2008), who observed AMEn improvement in young broilers fed diets supplemented with fumaric acid and sorbic acid, and also corroborate studies conducted by Ao et al (2009), in which citric acid increased the metabolizable dry matter and crude protein. However, Hernández et al (2006) observed no differences in the metabolization of total and ileal dry matter and crude protein in the 16 to 21 day-old period in broilers fed two levels of formic acid.…”
Section: Resultssupporting
confidence: 81%
“…The broilers fed diets supplemented with organic acids and not supplemented with PA had higher GEMC, DMMC, NMC and EEMC values (P<0.05), in comparison with those fed diets without the additives, partially corroborating Ao et al (2009), who found that citric acid increased dry matter and crude protein metabolizability. However, when the birds were fed a combination of phytogenic additives and organic acids, they had lower NMC in comparison with those without organic acids supplementation and with PA supplementation.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The results indicated that the TME n of low oligosaccharide soybean meal was significantly higher than that of conventional soybean meals. Ao et al (2009) reported a significant increase of AME n of corn-soybean meal diet by dietary supplementinggalactosidase. However, Irish et al (1995) removed up to 90% oligosaccharides from soybean meal using either ethanol extraction or exogenous -galactosidase.…”
Section: The Use Of Exogenous Enzymes To Increase the Nutritional Valmentioning
confidence: 99%
“…In other studies, they added enzymes in broiler diets and fed broilers for 21 d. Increases in chick growth rate and digestibility that were similar to those recorded in previous study were obtained when protease and -galactosidase were included in the diets. Ao et al (2009) did two trials to investigate the effects of -galactosidase supplementation and acidification of diets on nutrient digestibility and growth performance of broiler chicks fed corn-soybean meal diet. The data showed that dietary supplementation of -galactosidase significantly increased feed intake and weight gain of broiler chicks, which was further approved by increased AME n of the diets and digestibility of CP and NDF.…”
Section: The Use Of Exogenous Enzymes To Increase the Nutritional Valmentioning
confidence: 99%